Analytical model for predicting the junction temperature of chips considering the internal electrothermal coupling inside SiC metal–oxide–semiconductor field‐effect transistor modules. Issue 3 (1st February 2020) - Peng, Sun; Zhibin, Zhao; Yumeng, Cai; Junji, Ke; Xiang, Cui; Bing, Ji
Abstract : Owing to their excellent characteristics, silicon carbide (SiC) metal–oxide–semiconductor field‐effect transistor modules are expected to have broad application prospects in various types of power conversion equipment in the future. Accurate prediction of the internal chip junction temperature of SiC module is of great value for the usage of the modules in the power conversion equipment. In this study, taking the electrothermal coupling process, and the thermal characteristics of the chips into consideration, the power loss model under unipolar and bipolar sinusoidal pulse‐width modulation control was developed. A star‐shaped equivalent thermal network model based on virtual temperature was established. Moreover, an analytical junction temperature predicting model was proposed. To obtain the temperature dependence of static and dynamic parameters for the models, power device analyser was used, and the double pulse test bench was established. To validate the effectiveness and accuracy of the above models, the finite element method was used to calculate the junction temperature of a commercial 1200 V/300 A full SiC module under different working conditions. The results show that the relative error is very small and the proposed model is effective.